'Old wine in new bottles': Heteroglossia or (un)conscious (re)production in NS Puleng's poetry. Issue 1 (2nd January 2022) - Mokgoatšana, Sekgothe
Abstract : The purpose of this article is to raise an old debate that seeks to explore textual relations and how meaning is ascribed to texts. Is meaning finite? Is the author responsible for the meaning of the texts (s)he produces? The other question is whether heteroglossia implies a deliberate disruption and imitation of other texts. The article uses heteroglossia, a concept adapted by Julia Kristeva as 'intertextuality' to examine Sepedi poetry written by NS Puleng and examine 'transportations', and 'intertextual weavings' of other texts discernible in Puleng's poems. By doing this, the article revives the death of the author and the "birth of the reader" as old debates clothed in textual theories espoused by theorists such as Roland Barthes and Kristeva in their attack on the capitalist notions of readers as consumers and authors as producers and holders of knowledge. By using the analogy of 'old wine in new bottles', I demonstrate that the views of earlier theorists in language politics are still relevant today.